Virginia Woolf and Christian culture - De Gay, Jane, 1966- (Edinburgh : Edinburgh University Press, 2017)
This wide-ranging study demonstrates that Woolf, despite her agnostic upbringing, was profoundly interested in, and knowledgeable about, Christianity as a faith and a socio-political movement.
Machine generated contents note: 1. Family Background: Clapham and After -- 2. Contemporary Conversations -- 3. Reverend Gentlemen and Prophetesses -- 4. Sacred Spaces: Churches and Cathedrals -- 5. Domestic Sacred Spaces -- 6. Purple Triangle and Blue Madonnas: The Virgin Mary -- 7. How Should One Read the Bible?
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 29, 2018).
eBooks on EBSCOhost
Keywords: Woolf, Virginia, -- 1882-1941.; Woolf, Virginia, -- 1882-1941; Culture -- Religious aspects; Christianity -- 20th century; Christianisme -- 20e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; PERFORMING ARTS -- Acting & Auditioning; Christianity; Culture -- Religious aspects; 1900-1999